Analisis Produktivitas Tenaga Kerja pada Proyek Pembangunan Airlangga Edupreneur Center (AEC) Tahap 1 Universitas Airlangga dengan Metode Time Study - Utomo, Wahyu Agung Ponco Ndriyo Galih; Triana, Masca Indra (Jurnal Sains dan Teknologi (JSIT), 2025)
Human resources play a crucial role in the construction sector, particularly in achieving optimal productivity. Variations in labor productivity in reinforced concrete structural work, such as reinforcement, formwork, and casting, pose a significant challenge to improving project efficiency. This study aims to analyze actual labor productivity in reinforced concrete structural work at the Airlangga Edupreneur Center (AEC) building project, specifically focusing on Guest House 1. The method used is Time Study, where observations are made directly on-site to measure the time required for each activity. The analysis technique employed is the calculation of Basic Time and Standard Time to determine labor productivity. The results of the study show that labor productivity varies across different types of work. For reinforcement work, productivity ranged from 71.14 to 2,175.84 kg/OH, with the highest value in slab work and the lowest in small column work. For formwork, productivity ranged from 3.43 to 134.43 m²/OH, while for casting, it ranged from 20.11 to 243.02 m³/OH. These variations are influenced by factors such as job characteristics, structural complexity, labor quantity, implementation methods, site conditions, and worker skill levels. This study provides a quantitative overview of labor productivity in construction projects, which can be used as a reference for resource planning, project duration estimation, and work method efficiency evaluation.